Pengaruh Pembelajaran Aqidah Akhlak Terhadap Perilaku Peserta Didik Kelas V di SDIT Ar Rahman Bojonggede Bogor - Rois, Ajun; Rahma, Siti Aulia (At-Tadris: Journal of Islamic Education, 2024)
The purpose of this study is to analyze the influence of moral faith learning on the behavior of class V students at SDIT Ar Rahman Bojonggede Bogor. Learning Aqidah Akhlak is closely related to the formation of student behavior, for example subject matter about speaking ethics, so in this material students are taught how to speak to teachers, parents and fellow friends. This study uses this type of research quantitatively, with a descriptive method through the use of data collected from the results of questionnaire distribution and documentation. The respondents of this study are integrated Islamic elementary students at SDIT Ar Rahman Bojonggede Bogor. The sampling technique uses saturated sampling (census), namely all students in class V totaling 34 students. The results of this study show that the level of learning of moral beliefs in schools is in the strong category with a percentage of 65%.  This can be influenced by several supporting factors such as the existence of learning strategies in the formation of student morals. The level of Student Behavior at SDIT Ar Rahman Bojonggede Bogor is in the strong category with a percentage of 71%. This can be influenced by several factors such as the alignment of the rules in schools with the Aqidah moral learning materials. After the author conducted a study, there was a significant influence between moral aqidah education on the behavior of grade V students at SDIT Ar Rahman Bojonggede Bogor for the 2023-2024 Academic Year. This can be proven by hypothesis testing using a simple analysis test with a correlation test obtained a value of (0.850) which shows a very strong influence.